Degradation of AlGaN/GaN high-electron mobility transistors in the current-controlled off-state breakdown - Kuzmik, J.; Jurkovič, M.; Gregušová, D.; Ťapajna, M.; Brunner, F.; Cho, M.; Meneghesso, G.; Würfl, J. (Journal of applied physics, 2014)
We investigate degradation mechanisms in AlGaN/GaN HEMTs which were repeatedly driven into the current-controlled off-state breakdown or subject to 60 s voltage- or current-controlled off state stresses. The current-controlled sweep in to the breakdown allows the sustainability of breakdown that can not be observed in the voltage controlled sweep. Only temporal changes were observed in the HEMT dc performance after repetitive sweeps, which were explained by charging/discharging of the HEMT surface at the gate-to-drain access region and in the GaN buffer below the gate. Similar changes were observed also if high-voltage stress has been applied on the drain; however, permanent degradation appears after 60 s current-controlled breakdown stress. In this case, the drain leakage current, as well as the breakdown current, increases significantly. On the other hand, the breakdown voltage, as well as the gate characteristics, remains unaltered. We suggest that the avalanche-injection process is governing the off-state breakdown event with a dominant role of the potential barrier at the channel-buffer interface.